Springback Behavior of AA 7075-T6 Alloy in V-Shaped Bending - Çetin Karakaya; Seçil Ekşi (Applied Sciences)
Springback is the most fundamental problem in all sheet metal-forming processes. Springback is affected by many process variables, and material properties are at the forefront of these variables. This study investigated the effects of the forming process at elevated temperature, bending radius, bending angle, and sheet metal thickness on the springback properties of AA 7075 aluminum alloy sheet metal with finite element analyses. The effects of process parameters on springback and maximum load are investigated using ANOVA analyses. The results show that the bending radius is the most effective on springback (45.2%). Metal thickness is the second critical parameter for springback (28.1%). The third most important factor is the process temperature (19.9%). Metal thickness (84.21%) is the most effective parameter on the maximum load. The bending angle is the second most important parameter (6.88%).